Evaluation of HER2 Gene Status in Breast Cancer Samples with Indeterminate Fluorescence in Situ Hybridization by Quantitative Real-Time PCR - Koudelakova, Vladimira; Berkovcova, Jitka; Trojanec, Radek; Vrbkova, Jana; Radova, Lenka; Ehrmann, Jiri; Kolar, Zdenek; Melichar, Bohuslav; Hajduch, Marian (The Journal of molecular diagnostics, 2015)
Administration of drugs targeting HER2 (official symbol ERBB2) is an important component of therapy for breast cancer patients with HER2 amplification/overexpression as determined by in situ hybridization (ISH) and immunohistochemistry (IHC). In approximately 5% of breast cancers, ISH assays fail. In these cases, HER2 protein expression is evaluated by IHC alone that may yield false negatives/positives for poor-quality samples. Therefore, we developed a method that was based on quantitative real-time PCR applicable for DNA from formalin-fixed, paraffin-embedded tissue samples. Its limit of detection was determined with breast cancer cell lines and validated with 223 breast cancer patient samples. On the basis of comparisons with fluorescent ISH (FISH) and IHC data, the sensitivity of the new method was 94.2% and 95.1%, its specificity was 100% and 99.1%, and overall concordance between results obtained with the quantitative real-time PCR method and FISH/IHC was 97.6% for both methods. The quantitative real-time PCR method was then used to evaluate the HER2 status of 198 of 3696 breast cancer tissues that yielded indeterminate FISH results. The HER2 copy number was successfully determined in 69.2% of these indeterminate samples. Thus, the DNA-based technique appears to be a specific, sensitive method for determining HER2 copy numbers when the FISH assay fails, which may complement IHC tests.
Keywords: formaldehyd; regulace genové exprese u nádorů; Humans; Tumor Cells, Cultured; In Situ Hybridization, Fluorescence; zalévání tkání do parafínu; Biomarkers, Tumor; Immunoenzyme Techniques; Female; amplifikace genu; receptor erbB-2; lidé; nádorové buňky kultivované; nádorové biomarkery; imunoenzymatické techniky; Breast Neoplasms; ženské pohlaví; Gene Amplification; hybridizace in situ fluorescenční; Retrospective Studies; Paraffin Embedding; Receptor, ErbB-2; nádory prsu; Real-Time Polymerase Chain Reaction; retrospektivní studie; Gene Expression Regulation, Neoplastic; kvantitativní polymerázová řetězová reakce; Formaldehyde